1994
DOI: 10.1007/bf03160083
|View full text |Cite
|
Sign up to set email alerts
|

Brain content of glycosphingolipids after oral administration of monosialogangliosides GM1 and LIGA20 to rats

Abstract: Natural (GM1) and semisynthetic [113-Neu-5-AcGgOse4-2-D-erythro-1,3- dihydroxy-2-dichloroacetylamide-4-trans-octadecene (LIGA20)] glycosphingolipids, given parenterally, protect neurones against glutamate-induced death without producing the side effects typical of glutamate receptor antagonists. Chronic glutamate-related neurotoxicity (e.g., in recurring strokes in elderly hypertensive patients, and in Parkinson disease) could be prevented also by glycosphingolipids treatment, but this therapeutic intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Since the LIGA20 plasma levels are 4-to 6-fold greater than that of brain (22,23), one can presume that the drug concentration in the brain may not be uniform and perhaps may be higher in the surroundings of the infarcted area due to local changes in the blood-brain barrier. A protracted treatment combining i.v.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the LIGA20 plasma levels are 4-to 6-fold greater than that of brain (22,23), one can presume that the drug concentration in the brain may not be uniform and perhaps may be higher in the surroundings of the infarcted area due to local changes in the blood-brain barrier. A protracted treatment combining i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bioavailability of LIGA20 given orally to rats is at least 2 orders of magnitude greater than that of GM1 (22). Moreover, recent studies demonstrated that LIGA20 is slowly metabolized, and after a single oral administration a measurable brain content of this drug is maintained for longer than 48 hr (22). In addition, the parenteral or oral administration of LIGA20 to rats, before the induction of a photochemical brain infarct, exerts a strong neuroprotective action against glutamateinduced neurotoxicity in the areas that surround the region of maximal ischemic damage (10).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Oral administration of LIGA 20 protects neurons against glutamate-induced neuronal death in rats without producing the side effects typical of glutamate receptor antagonists (173) and in mice subject to kainate-induced seizures and apoptosis (174). The level of LIGA 20 in brains of treated animals can reach a significantly higher level than can GM1; moreover, animals treated with LIGA 20 showed no apparent biochemical or behavioral adverse effects (173,175), suggesting that this compound may be useful as a neuroprotective agent in neuronal cell death in AD.…”
Section: Therapeutic Potentials Of Gangliosides In Patients With Admentioning
confidence: 99%